THE IMPLEMENTATION OF ICT-INTEGRATED ELT ACROSS CURRICULUM 2013 IN SENIOR HIGH SCHOOLS IN PALEMBANG - Dianti, Rahma; Atmanegara, Yunani (English Community Journal, 2018)
Infusing technology into English Language Teaching can contribute positive impacts toward students’ learning if it is integrated in such a way. Curriculum 2013 proposes the integration of Information Communication Technology into instructional practices. This study investigatedwhether or not the teachers of English integrated ICT into their ELT; described about how ICT was implemented in ELT; and explored the obstacles faced by the teachers of English in implementing ICT. This study surveyed ten state Senior High Schools in Palembang. Twelve teachers of English and 200eleventh grade students participated in this study chosen by using purposive samplingtechnique. In gathering the data, questionnairewas administered. The results showed that most English teachers and students integrated ICT in their classroom. ICT was implemented as instructional tools to facilitate English learning in the classroom. However, they still faced some obstacles in integrating ICT into ELT. School supports became the main factor hindering ICT implementation at schools.